HYGIENE DAN KESEHATAN LINGKUNGAN - Siti Rokayah; Gunawan Widjaja (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This research aims to analyze the Hygiene and Health Environment. This research is normative juridical research that is descriptive in nature and uses a prescriptive form with the aim of problem-solving. The data used is secondary data which was analyzed qualitatively. The results of this study indicate that the definitions and regulations governing Hygiene and Health Environment overlap each other.